MICROBACIAS II: ERROS E ACERTOS DA GESTÃO PÚBLICA E PRIVADA - ESTUDO DE CASO FAOP - Alessandra; Alexandre Godinho (Universidade do Oeste Paulista, 2015)
Selective projects are carried out with public resources that aim the economic and social development focused on rural agriculture. Among the agricultural activities in the area, fruitgrowing has been highlighting in agricultural productivity of Oeste Paulista. Micro-basins II is a modern instrument of public policy and the FACIC Jr has approved a business plan for the construction of reception Centers and a depulper in the area of Presidente Prudente. This article demonstrates the gains, the problems and the economic consequences of unfolding the implementation of this business plan, as well as the importance of planning and professionalism for achieving efficient results. The main objective was to monitor the proposal of FAOP by the Micro-basins II. The results showed that the problems came from the difficulty of management, lack of information and mainly from bureaucratization. The results confirmed the thesis of remarkable authors on the subject, who claim that it is not enough to obtain public resources, policies should have adherence and effective internal management to improve efficiency in the area. The methodology was based on a qualitative approach, bibliographic research and public and juridical sites.